2018
DOI: 10.1111/jfb.13556
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression analysis of tyr and tyrp1 genes in normal and albino yellow catfish Tachysurus fulvidraco

Abstract: The full-length complementary DNA of two genes related to vertebrate albinism, the tyrosinase gene tyr and tyrosinase-related protein 1 gene tyrp1, were cloned and analysed from normal and albino yellow catfish Tachysurus fulvidraco. The open reading frames (ORF) of tyr and tyrp1 encode putative peptides of 533 and 526 amino acids (amino-acid), both of which possess two conserved copper binding sites. The homologous identities of deduced amino-acid sequences showed that both Tyr and Tyrp1 of T. fulvidraco shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In French cattle breeds, the greatest expression of TYRP1 occurred in the black skin of Prim'Holstein cattle; in the pheomelanin-rich coats of the Blonde d' Aquitaine (blond), Limousin (red), and Salers (reddish brown) breeds, there were varying levels of complete repression of TYRP1 55 . In catfish, lower expression levels of TYRP1 mRNA were detected in the albino yellow group than in the black wild-type group 56 . These results provide useful data for understanding the relationship between the lower expression of TYRP1 and the pheomelanin-based phenotype.…”
Section: Discussionmentioning
confidence: 88%
“…In French cattle breeds, the greatest expression of TYRP1 occurred in the black skin of Prim'Holstein cattle; in the pheomelanin-rich coats of the Blonde d' Aquitaine (blond), Limousin (red), and Salers (reddish brown) breeds, there were varying levels of complete repression of TYRP1 55 . In catfish, lower expression levels of TYRP1 mRNA were detected in the albino yellow group than in the black wild-type group 56 . These results provide useful data for understanding the relationship between the lower expression of TYRP1 and the pheomelanin-based phenotype.…”
Section: Discussionmentioning
confidence: 88%
“…Melanin is the most important pigment in animal skin, and can be divided into eumelanin (black or brown) and pheomelanin (yellow or red) based on differences in phenotype 41 . SLC7A11 , also known as xCT , is a cysteine/glutamate exchanger that mediates the cellular uptake of cysteine (a component of pheomelanin) and thus directly affects pheomelanin synthesis 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The tyr gene, which is synthesised in the endoplasmic reticulum and modified by the Golgi apparatus, then participates in the hydroxylation and oxidation processes of Levodopa (L‐DOPA) to form dopaquinone, and its ultimate activity determines the rate of melanin production, is the most important of the three genes 127 . Zhang et al 128 found the tyr gene was differentially expressed during the embryonic development of yellow catfish ( Tachysurus fulvidraco ), with a pattern of gradually increasing from low to maximum and then decreasing, peaking as the skin and fins began to form a mass of melanin; furthermore, they discovered that when the tyr gene was mutated, the skin colour turned golden yellow. In the early embryonic development of koi carp, Yin et al 129 observed that tyr mRNA peaked in the gastrula and blastula stages, which involved the formation of body colour.…”
Section: Genetic Basis and Molecular Mechanisms For Fish Skin Colourmentioning
confidence: 99%